Impact of Work Motivation, Physical Work Environment, and Compensation on Job Satisfaction on Employees of PT. Kiandra Alam Semesta - Zahara, Siti; Wijaya, Fanji; Supiyadi, Dedi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Job satisfaction for employees in a company is very important because it will directly or indirectly affect the continuity of employees' work. If employees are dissatisfied with their work, negative attitudes towards work will emerge, such as a lack of employee motivation, the employee's desire to look for another more unbalanced job or a new one, and other complaints. The impetus for conducting this research was to know how work motivation, physical work environment, and encouragement influence employee job satisfaction. Participants in this research survey were employees of PT. Kiandra Alam Semesta, numbering 30 people. Sampling in this study used a saturated sampling technique. Questionnaires were sent to research participants as part of the quantitation methodology. Data analysis procedures include validity and reliability tests. Statistical studies using various regression formulas, partial tests, simultaneous tests, and coefficients of determination are used for descriptive and verification purposes. Based on findings at PT. Kiandra Alam Semesta, together Work Motivation (X1), Physical Work Environment (X2), and Compensation (X3) have a significant influence on the Level of Job Satisfaction (Y)